معالجة الشرى المزمن الأساسي باللوراتادين والأستيميزول - دلول محمود (Latakia University Journal -Medical Sciences Series, 2019)
يهدف هذا البحث إلى دراسة فعالية اللوراتادين والأستيميزول في معالجة الشرى المزمن الأساسي. دخل في الدراسة 92 مريضاً، 4 منهم لم يكملوا الدراسة. وزع المرضى 88 الباقون على ثلاث مجموعات: المجموعة الأولى تألفت من 30 مريضاً تناولوا اللوراتادين 10 ملغ مرة واحدة يومياً؛ المجموعة الثانية 29 مريضاً تناولوا الأستيميزول 10 ملغ مرة واحدة يومياً؛ والمجموعة الثالثة 29 مريضاً تناولوا الدواء الغفل (Placebo) لمدة أربعة أسابيع. تم تقييم الأعراض والعلامات (العدد الكلي للآفات، حجم الآفات، عدد النوب المنفصلة، الحكة) بشكل أسبوعي من قبل الباحث وبشكل يومي من قبل المريض. قيم الباحث الفعالية الكلية للمعالجة حسب درجات هي: 0 = عدم تحسن؛ 1 = تحسن طفيف؛ 2 = تحسن ملحوظ؛ 3 = فعالية عالية؛ 4 = زوال تام للأعراض والعلامات. كان متوسط عمر المرضى 36.1 سنة منهم 38.64% ذكور و 61.36% إناث. بينت الدراسة بأن كلاً من اللوراتادين والأستيميزول كانا أكثر فعالية بكثير من الدواء الغفل، إلا أن اللوراتادين أدى إلى تحسن الأعراض والعلامات خلال 24 ساعة الأولى بالمقارنة مع الدواء الغفل، بينما تفوق الأستيميزول على الدواء الغفل في اليوم الثاني. كان اللوراتادين أفضل من الاستيميزول بالنسبة لعدد الآفات والحكة وحجم الآفات خلال الأيام الخمسة الأولى من الدراسة. بين التقييم الإجمالي في نهاية المعالجة أن المعالجة بكل من اللوراتادين والأستيميزول أكثر فعالية بكثير من الدواء الغفل. أكثر التأثيرات الجانبية شيوعاً أثناء المعالجة كانت الصداع والوسن والتعب وجفاف الفم. كان كلاً من اللوراتادين والأستيميزول فعالاً في علاج الشرى المزمن الأساسي مع نسبة تأثيرات جابية متشابهة. ولكن الفائدة السريرية كانت أسرع بشكل واضح مع اللوراتادين. The objective of this article is to study the effect of loratadine and astemizole in the treatment of chronic idiopatic urticaria. This work took place on 92 patients in Al-Asad Univercity Hospital in Lattakia. 4 patients were withdrawn from treatment befor they completed the trial. The remaining 88 patients with chronic idiopatic urticaria were randomly assigned to relieve either 10 mg loratadine daily (30 patients), 10 mg astemizole daily (29 patients), or placebo (29 patients) for 4 weeks. Patients rated symptoms and signs (total number of lesions, size of lesions, number of separated episodes, and pruritus) each night, and investigator rated symptpms weekly. At the final visit investigator evaluated the overall efficacy of treatment on the following rating scale: 0 = no improvement or worse, 1 = slight but insufficient improvement, 2 = definite improvement, 3 = treatment highly effective, and 4 = complete disappearance of signs and symptoms. Mean age of patients was 36.1 years, of them 61.36% hemale and 38.64% male. Both loratadine and astemizole were significantly superior to placebo in relieve symptoms of chronic idiopatic urticaria. Loratadine reduced all signs and symptoms within 24 hours of the first dose compared with placebo. In contrast, astemizole failed to show signifigant activity versus placebo until 2 days for pruritus and 3 days or longer for the other signs and symptoms. Loratadine was signifigantly better than astemizole for number of lesions, prurritus, and size of lesions on day1 through days 4 and 5. Results of global assessment at the end of treatment indicated that both loratadine and astemizole were more actively than placebo. The most frequent side- effects of treatment were headache, somnolence, fatigue, and dry mouth. Both loratadine and astemizole provide effective relief of the symptoms of chronic idiopatic urticaria with similar side-effect profiles. However, clinical benefit occurs significantly more rpidly with loratadine